Fish stock demographics of skipjack tuna (Katsuwonus pelamis) from Kavaratti in Lakshadweep, Southern Arabian Sea - Muhsin, Aliyyathumada Ishyyapura; Shahul Hameed, Pentam Veli Pura; Pookoya, Pathummathada; Harikrishnan, Mahadevan; Ranjeet, Kutty (Journal of Fisheries, 2020)
Marine fish stocks are depleting at an alarming rate. Skipjack tuna, Katsuwonus pelamis has been exploited in Lakshadweep Island area in the Indian Ocean mainly by pole and line fishery which constituted one-third of its production in the country. Age, growth, demographics and stock assessment of this species were investigated from the Lakshadweep waters. The von Bertalanffy growth factors were estimated as asymptotic length 72.5 cm, growth constant 0.480 and the theoretical age at zero-length as –0.1097. This study showed that skipjack grows from 30 to 68.26 cm from first to sixth year. The natural mortality, fishing mortality and total mortality were 0.82, 1.51 and 2.33 respectively. The exploitation ratio was 0.65, while the exploitation which maximises relative yield per recruit (Emax) was 1.0. Recruitment pattern showed that young recruits entered the fishing grounds in most months, with peaks during June–July. Length based Virtual Population Analysis indicated that the major loss in its stock up to 22 cm was due to natural causes. At the same time, higher fishing mortality was registered in 40–60 cm length group. The present study provides knowledge on the demographics of K. pelamis, pertinent for formulating an effective fisheries management in the region.